Manajemen Dakwah dalam Perspektif Sayyid Qutb - Muhammad Halif Asyroful Bahana (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2025)
Da’wah management is a discipline that discusses how da’wah activities can be carried out systematically, effectively, and sustainably. One of the most influential figures in da’wah thought is Sayyid Qutb, known for his revolutionary and activist approach. His ideas, mostly articulated in Fi Zhilal al-Qur’an, emphasize that da’wah is an effort toward social transformation, requiring the total implementation of Islam in life. This article explores how Sayyid Qutb’s da’wah concepts impact Islamic da’wah management. Using a qualitative approach and literature study method, this research highlights aspects of da’wah management, its roles and functions, and its relevance in the context of modern da’wah.